Serbian National Identity through the Prism of Saint Sava’s Cult and Kosovo Covenant - Lunić, Tomislav; Lunić, Duško (Napredak, 2022)
Since the topic we have addressed is a common source of the inspiration for poets, enthusiasts and artists from various areas, it was not easy to formulate and adjust it to the strictly scientific approach. In that respect, we would like to say that certain parts of the text are fiction and subject to fascinations that cannot be scientifically defined, but have an important role in cultural and historical terms and constitute an important factor in the formation of the Serbian national identity. In the first part of the text we review Saint Sava’s role in taking the Serbian people into Orthodox Christianity. The emphasis is on the role of the Church that has followed the Serbian people throughout its suffering, giving its comfort and the feeling of safety. Belonging to the ecumenical family of Orthodox Christianity was and has remained the priority. Furthermore, we point to the significance of Kosovo covenant. Prince Lazar and his noblemen made a sacrifice for the Serbian nation on the whole and, metaphorically speaking, he carved his name in Christ’s book of eternity. In the last part of the paper we draw the parallel between Saint Sava’s cult and Kosovo covenant which, on one hand, represent the object of imagination and artistic fascination, while, on the other hand, they play an important symbolic role in the creation of the Serbian national identity.
Keywords: Saint Sava’s cult; Kosovo covenant; Prince Lazar; Jesus Christ